An exploratory study on the challenges faced by orphans and vulnerable children (OVC) in the schools of Maleboho East Circuit of the Capricorn District of Limpopo Province to develop a multi-disciplinary model - Ntjana, Ngwanamontjane Eglesia (My University, 2023)
Society faces the serious challenges of having to find solutions to look after orphaned and vulnerable children (OVC), who often survive against all odds, and are exposed to more threatening or challenging environments than other children. Although this is a widespread and global problem, in sub-Saharan Africa it is exacerbated by other precarious social conditions such as poverty, unemployment, inequality and domestic violence, among other factors. South Africa is no exception to these challenges. Being a developing country, it is still faced with an escalating problem of vulnerable children. This scenario is complicated by the fact that the scope of vulnerable children is vast and complex, but OVCs form the most vulnerable group, as they experience multiple dimensions of vulnerabilities. The South African Government took a positive step and responded with a series of legislations, policies and programmes to mitigate the vulnerability of children. However, despite these responses, the issue of vulnerability continues to grow. In schools, vulnerability makes it extremely difficult for OVC to cope with the demands of academic work and causes them to repeat their grades several times. The present study explored the challenges facing OVC in schools of the Maleboho East Circuit. The communities around the Maleboho East Circuit are termed multi-risks communities, where social issues such as poverty, unemployment, inequality and substance abuse are prevalent. The study anchored itself on ecosystem theory, emphasising the importance of a person in context, strength-based, which was a shift from deficiencies to strengths and resilience theory. This approach provided a lens and mind map that guided the study. This was paramount for a study of this nature, as the problems experienced by the child at home will eventually cascade into the school environment, where academic performance is needed. The three theories were complementary to each other, as they were used to compensate each other’s deficiencies. The study followed an interpretive paradigm, which placed emphasis on the participants’ lived experiences. In a study such as this one, where in-depth data was required; this paradigm allowed the researcher to enter the participants’ lived world through a focus group discussion and personal interviews. From the interviews, themes and sub-themes were generated that were informed by the participants’ responses. Findings indicated that the OVC face many challenges both in school and in their homes as well as their communities. In their homes, they are heavily burdened with household chores that consume most of their time, making it difficult for OVC to juggle both household duties and academic work, causing serious barriers that hinder their academic progress, and results in them often failing and repeating their grades multiple times. They are also challenged by other psychosocial issues such as anger and frustration, and emotional difficulties caused by their lack of basic and school necessities. Though faced with these challenges, they developed their own coping strategies to manage their situation. However, the researcher concluded that the OVC’s challenges made them feel and become educationally excluded. As most OVC are coming from impoverished homes, they will fail to break the intergenerational cycle of poverty they are subjected to. Therefore, the researcher recommended that the government as a custodian of children’s welfare should create an environment that is more conducive for the policy for inclusive education to be implemented. Schools should adopt a responsibility, where the focus is not only on education, but on creating an environment where all learners will be catered for holistically, irrespective of their background, thereby enabling them to become better citizens of tomorrow. This is in line with the spirit of the Constitution of South Africa, 1996.
Thesis (Ph.D. (Social work)) -- University of Limpopo, 2023
Keywords: High-risk conditions; Multi-risks communities; Orphans and Vulnerable Children; Vulnerability; Orphans; Vulnerability (Personality trait); Child welfare -- South Africa -- Limpopo